The night garden - Horvath, Polly (Square Fish, 2019)
During World War II, twelve-year-old Franny lives contentedly with her parents Sina and Old Tom near a mysterious garden that supposedly grants everyone one wish. But after their neighbor drops off her three children in order to investigate her suspicions about her husband, Franny learns of dark secrets about him, and she and the children must decide if using the magical night garden is worth the risk.